Dari Downing Street ke Wall Street : Taksonomi Awal untuk Strategi Penerjemahan Metonimi Nama Tempat - Adam, Muhammad (Kementerian Sekretariat Negara Republik Indonesia, 2020)
A place name generally is translated from source text into the target text by preserving it, but when it is used as metonymy, it will need another strategy, as it carries additional contextual references and inferences. The translation of metonymy has been widely discussed from figurative translation method to cognitive approach, all agrees on the cultural context which is embedded in metonymy. This paper aims to propose strategies in translating place name metonymy which is most unlikely to be preserved during translation and to suggest taxonomy of possible result. The translation will adopt strategy from Baker (2011) description on translating non-equivalence at word level. The study is descriptive qualitative. The result shows that the place name metonymy will not be preserved as it is and shall be translated with possible strategies such translation by general words and loan words plus explanation. Thus, the place name metonymy is most likely lost during translation. Keywords: Metonymy Translation; Place Name Metonymy; Cultural Context.